2017
DOI: 10.1037/ppm0000087
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory motivations in celebrity interest: Self-suppression and self-expansion.

Abstract: Due to concerns regarding the theoretical and empirical contexts that surround the description of celebrity interest, the current studies examined the development of a measure of 2 self-regulatory motivations in celebrity interest (RMiCI): self-suppression and self-expansion. Across 2 samples (total n ϭ 527), scores on an adapted version of Stenseng, Rise, and Kraft's (2012) Escapism Scale demonstrated a replicable 2-factor structure, concurrent and convergent with other measures of celebrity interest and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Consistent with prior scholarship (e.g. Ganideh & Good, 2015;Maltby & Day, 2017), the current research found users' self-escapism motivation to engage in e-shopping a two dimensional construct made up of self-suppression and self-expansion motivations. Results indicate that users engage in e-shopping activities like browsing product content and using e-carts on e-tailing websites such as daraz.com to regulate the negative-self caused by poor circumstances.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with prior scholarship (e.g. Ganideh & Good, 2015;Maltby & Day, 2017), the current research found users' self-escapism motivation to engage in e-shopping a two dimensional construct made up of self-suppression and self-expansion motivations. Results indicate that users engage in e-shopping activities like browsing product content and using e-carts on e-tailing websites such as daraz.com to regulate the negative-self caused by poor circumstances.…”
Section: Discussionsupporting
confidence: 87%
“…The motive behind self-expansion R M B R motivation is to maximize well-being. These dimensions of self-escapism motivation have been researched in the areas such as sports and celebrity interest (See Al Ganideh & Good, 2015;Maltby & Day, 2017). The current research offers that self-suppression and self-expansion motivations drive users' e-shopping engagement behaviour.…”
Section: Proposed Modelmentioning
confidence: 72%
“…Reyes et al (2016) found that CAS scores correlated negatively with scores on a mental health measure, although this correlation was weak. Maltby and Day (2017) found that entertainment-social CW correlated with positive affect while borderline-pathological CW correlated with negative affect; interestingly intense-personal CW showed a correlation with negative affect but also a weaker, though still significant, correlation with positive affect. In the same study, celebrity interest for self-expansion reasons correlated positively with positive affect, while celebrity interest for self-suppression reasons correlated positively with negative affect.…”
Section: Attitudes Towards Eatingmentioning
confidence: 87%
“…McCutcheon et al (2015) found significant positive correlations between the two higher levels of CW and the need for uniqueness. Maltby and Day (2017) explored correlations between CAS scores and scores on a biopsychological personality measure. Entertainment-social and intense-personal CW were both positively associated with reward responsiveness (motivations in anticipation of future rewards); no CAS sub-scales were correlated with drive (goal-directed motivations), funseeking (willingness to approach new situations spontaneously), anxiety/inhibition relating to failure to reach goals, or fear/concerns about anticipated punishment.…”
Section: Othermentioning
confidence: 99%
“…Fans' attachment towards celebrities takes several degrees and levels of intensity. For instance, [37] in a recent study revealed that people who worship celebrities (celebrity worship) for intense-personal reasons are inclined to being unaware that in any given context, there are available options and alternatives; are unwilling to be flexible; demonstrate low selfefficacy in being flexible and have low cognitive flexibility. Based on the preceding discussions, it can be argued that attachment theory is very relevant as far as the relationship and interaction between celebrities and fans on social media is concerned.…”
Section: Attachment Theorymentioning
confidence: 99%